The trajectories of student emotional engagement and school burnout with academic and psychological development: Findings from Finnish adolescents. (April 2015) - Wang, Ming-Te; Chow, Angela; Hofkens, Tara; Salmela-Aro, Katariina
Abstract: The present study examined the longitudinal trajectories of emotional engagement and school burnout in Finnish adolescents from 9th to 11th grade and how these trajectories related to the development of adolescents' academic performance and depressive symptoms. We found that despite their high academic performance, Finnish adolescents experienced a decline in the overall quality of their emotional engagement with school as they moved from 9th to 11th grade. Specifically, Finnish adolescents found school less enjoyable and less valuable, becoming more overwhelmed and anxious about school with the passing years. In addition, emotional engagement and school burnout had distinct trajectories and longitudinal associations with academic and psychological wellbeing. These findings underscore the importance of examining both positive and negative emotional processes in order to improve understanding of student emotional engagement and its differential effect on adolescent development. Highlights: Finnish adolescents' trajectories of emotional engagement and school burnout vary. Emotional engagement includes positive and negative processes. Finnish students experienced a decline in their emotional engagement with school. Emotional engagement predicted academic performance and depressive symptoms.